Respuesta :
x2 – 4x – 12 A) (x – 6)(x + 2)
x2 + 4x – 12 B) Prime
x2 – x – 12 C) (x – 4)(x + 3)
x2 – 7x – 12 D) (x – 2)(x + 6) i think this is the awnser:)
Answer:
[tex]x^2-4x-12\ ------------------\ (x+2)(x-6)\\\\x^2+4x-12\ -----------------\ (x-2)(x+6)\\\\x^2-x-12\ -------------------\ (x-4)(x+3)\\\\x^2-7x-12\ ------------------\ Prime[/tex]
Step-by-step explanation:
1)
[tex]x^2-4x-12[/tex]
This could be factored by using the method of splitting the middle term.
i.e.
[tex]x^2-4x-12=x^2-6x+2x-12\\\\i.e.\\\\x^2-4x-12=x(x-6)+2(x-6)\\\\i.e.\\\\x^2-4x-12=(x+2)(x-6)[/tex]
2)
[tex]x^2+4x-12[/tex]
This could again be factored by the method of splitting the middle term as follows:
[tex]x^2+4x-12=x^2+6x-2x-12\\\\i.e.\\\\x^2+4x-12=x(x+6)-2(x+6)\\\\i.e.\\\\x^2+4x-12=(x-2)(x+6)[/tex]
3)
[tex]x^2-x-12[/tex]
This could be factored by using the method of splitting the middle term.
i.e.
[tex]x^2-x-12=x^2-4x+3x-12\\\\i.e.\\\\x^2-x-12=x(x-4)+3(x-4)\\\\i.e.\\\\x^2-x-12=(x-4)(x+3)[/tex]
4)
[tex]x^2-7x-12[/tex]
This polynomial could not be factored.
Hence, it is a prime expression.